Manufacturing method of high-voltage electrostatic generator cable and high-voltage electrostatic generator cable

By setting a conductive adhesive layer and a sheath layer outside the inner core of the multi-aryl fiber of the high-voltage electrostatic generator cable, the problem of the cable being easily broken down in the high-voltage electrostatic field is solved, and efficient protection and normal operation of the cable is achieved.

CN119724760AInactive Publication Date: 2025-03-28HANGZHOU CHUANKOU SPECIAL WIRE & CABLE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411909129.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The high-voltage electrostatic generator cable is easily broken down in the electrostatic field, causing cable failure and affecting the normal operation of the circuit.

Method used

A polyaryl fiber inner core is used, and a conductive adhesive layer is extruded on its outside, including conductive particles, resin matrix, dispersing additives and additives, and a layer of polyethylene inner sheath layer and polyvinyl chloride outer sheath layer are further coated.

Benefits of technology

Through the presence of the conductive adhesive layer, the electric field stress is relieved, the cable medium is prevented from being broken down, the cable's high-voltage electrostatic field resistance is improved, and the cable's normal operation is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724760A_ABST
    Figure CN119724760A_ABST
Patent Text Reader

Abstract

The invention discloses a manufacturing method of a high-voltage electrostatic generator cable and the high-voltage electrostatic generator cable. The manufacturing method of the high-voltage electrostatic generator cable comprises the following steps: manufacturing a multi-aryl fiber inner core; extruding a polyethylene insulating layer outside the multi-aryl fiber inner core, wherein the extrusion temperature of the polyethylene insulating layer is 170-190 DEG C; extruding a conductive adhesive layer outside the polyethylene insulating layer, wherein the conductive adhesive layer comprises conductive particles, a resin matrix, a dispersing additive and an auxiliary agent; extruding a polyethylene inner sheath layer outside the conductive adhesive layer, wherein the extrusion temperature of the polyethylene inner sheath layer is 170-190 DEG C; and the polyvinyl chloride outer sheath layer is extruded outside the polyethylene inner sheath layer, and the extrusion temperature of the polyvinyl chloride outer sheath layer is 125-160 DEG C. Through the arrangement, the cable can be prevented from being broken down by a high-voltage electrostatic field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of cable technology, and in particular to a method for manufacturing a high-voltage electrostatic generator cable and a high-voltage electrostatic generator cable. Background Art

[0002] High-voltage electrostatic generator is also called electrostatic flocking device. The principle of electrostatic flocking is to use the physical property that like charges repel each other and opposite charges attract each other to make the fluff carry negative charge. The object to be flocked is placed under zero potential or grounding conditions. The fluff is attracted by the object with different potential and accelerates vertically to the surface of the object to be flocked. Since the object is coated with adhesive, the fluff is vertically stuck to the object.

[0003] The cable of the high-voltage static generator is in an electrostatic field, which may cause the insulation layer of the cable to be broken down, causing cable failure. Under high voltage conditions, the strength of the electric field may exceed the tolerance of the insulation layer, causing electrical breakdown between the insulation layer and the inner and outer conductors. This will cause a short circuit or open circuit in the cable, which in turn affects the normal operation of the entire circuit. Summary of the invention

[0004] In order to solve the deficiencies of the prior art, the purpose of the present application is to provide a method for manufacturing a high-voltage electrostatic generator cable and a high-voltage electrostatic generator cable, which can prevent the cable from being broken down by a high-voltage electrostatic field.

[0005] To achieve the above objectives, this application adopts the following technical solutions: The present application provides a method for manufacturing a high-voltage electrostatic generator cable, which comprises: manufacturing a polyaromatic fiber inner core; extruding a polyethylene insulation layer outside the polyaromatic fiber inner core, wherein the extrusion temperature of the polyethylene insulation layer is 170-190°C; extruding a conductive adhesive layer outside the polyethylene insulation layer, wherein the conductive adhesive layer comprises conductive particles, a resin matrix, a dispersing additive and an auxiliary agent; extruding a polyethylene inner sheath layer outside the conductive adhesive layer, wherein the extrusion temperature of the polyethylene inner sheath layer is 170-190°C; and extruding a polyvinyl chloride outer sheath layer outside the polyethylene inner sheath layer, wherein the extrusion temperature of the polyvinyl chloride outer sheath layer is 125-160°C.

[0006] As a preferred technical solution, the manufacture of the polyaromatic fiber core includes preparing the polyaromatic fiber, and the preparation of the polyaromatic fiber includes: preparing a high molecular weight p-phenylenediamine terephthaloyl chloride polymer; preparing the polyaromatic fiber by a liquid crystal spinning process; The method for preparing a high molecular weight terephthaloyl chloride-p-phenylenediamine polymer comprises: performing a polycondensation reaction of p-phenylenediamine and terephthaloyl chloride: Step 1, adding anhydrous lithium chloride, N-methylpyrrolidone and hexamethylphosphoric triamide into a reactor in proportion; Step 2, adding p-phenylenediamine, starting the stirrer, and stirring at room temperature until the p-phenylenediamine is fully dissolved; Step 3, cooling to 0°C-15°C, adding the first batch of terephthaloyl chloride, and continuing to stir for a certain period of time to allow terephthaloyl chloride and p-phenylenediamine to fully react; Step 4, cool down to 0°C-15°C again, add the second batch of terephthaloyl chloride, and stir rapidly. The reaction system will show the phenomenon of climbing rods and gelling, and then the gel will be broken. At this time, the reaction should be stopped; Step 5, subjecting the reaction product in step 4 to precipitation filtration, washing and drying to remove unreacted raw materials and by-products, and obtaining a high molecular weight terephthaloyl chloride-p-phenylenediamine polymer.

[0007] As a preferred technical solution, the preparation of polyaromatic fibers by liquid crystal spinning process includes: dissolving the prepared p-phenylenediamine terephthaloyl chloride polymer in a sulfuric acid solvent to form a liquid crystal solution; The spinning process is carried out by using a dry-jet-wet spinning process. During the spinning process, the liquid crystal solution is extruded from the spinneret hole, and the liquid crystal macromolecules are oriented themselves when passing through the air layer to obtain highly oriented polyaromatic fibers. The obtained polyaromatic fiber is subjected to water washing and neutralization treatment; The neutralized polyaromatic fiber is wound up and dried under traction.

[0008] As a preferred technical solution, the preparation of polyaromatic fibers by liquid crystal spinning process also includes: The dried polyaromatic fiber is heat-treated in a nitrogen atmosphere at a temperature of 380° C.-420° C. to improve the crystallinity of the polyaromatic fiber and the heat resistance of the polyaromatic fiber.

[0009] The present application also provides a high-voltage electrostatic generator cable, which includes: a polyaromatic fiber inner core, an insulating layer, a conductive adhesive layer and a sheath layer; the insulating layer is coated on the outside of the polyaromatic fiber inner core; the conductive adhesive layer is coated on the outside of the insulating layer, and the conductive adhesive layer includes 40 to 50 parts of conductive particles, 35 to 45 parts of a resin matrix, 4 to 6 parts of a dispersing additive and 8 to 12 parts of an auxiliary agent by mass; the sheath layer is coated on the outside of the conductive adhesive layer.

[0010] As a preferred technical solution, the conductive particles include one or more of powdered gold, silver, copper, aluminum, zinc, iron and nickel, graphite, and conductive metal oxides; the resin matrix includes one or more of epoxy resin, silicone resin, polyimide resin, phenolic resin, polyurethane, and acrylic resin.

[0011] As a preferred technical solution, the conductive particles include silver powder and copper powder in a mass ratio of (30-40): (60-70); the resin matrix includes cyclopentane resin and acrylate resin polyvinyl chloride in a mass ratio of (30-40): (60-70).

[0012] As a preferred technical solution, the dispersing additive is carbon nanotubes.

[0013] As a preferred technical solution, the auxiliary agent includes one or more of a stabilizer, a plasticizer, and a catalyst.

[0014] As a preferred technical solution, the sheath layer includes an inner sheath layer and an outer sheath layer, the outer sheath layer is coated on the outside of the inner sheath layer, the inner sheath layer is made of polyethylene, and the outer sheath layer is made of polyvinyl chloride.

[0015] Compared with the prior art, the beneficial effects of this application are: The present application can reduce the electric field stress and prevent the cable medium from being broken down by providing a layer of conductive glue outside the polyaromatic fiber core. The principle is as follows: After the conductive particles in the conductive adhesive are cured or dried, the isolation layer between the conductive particles becomes very thin due to the volatilization of the solvent and the curing of the adhesive. According to the tunneling effect of quantum mechanics, free electrons may pass through these thin isolation layers to form a conductive path, making the conductive adhesive conductive. When the conductive particles filled in the conductive glue reach a certain volume, they will contact each other to form an electronic continuity state. This state allows the free electrons on the conductive particles hit by external electromagnetic waves to move freely, forming an electromagnetic field opposite to the external electromagnetic field, thereby canceling each other out and achieving the effect of weakening electromagnetic interference waves. When electromagnetic waves hit the free electrons of the conductive glue, heat will be generated due to the certain resistance of the conductive particles. This energy conversion process follows the law of conservation of energy, that is, the energy of the electromagnetic interference wave is converted into heat energy, thereby weakening the electromagnetic interference wave. Due to the insulating properties of the resin matrix of the conductive adhesive, it can be considered that there is no direct contact between the conductive particles. Only through electron jumping between the conductive particles can electrons pass through the insulating layer and achieve the conduction effect (i.e., tunneling effect). BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a schematic diagram of the structure of the high-voltage electrostatic generator cable for this application; Wherein: 1. polyaromatic fiber inner core; 2. insulating layer; 3. conductive adhesive layer; 4. inner sheath layer; 5. outer sheath layer. DETAILED DESCRIPTION

[0017] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the specific implementation manner of the present application will be clearly and completely described below in conjunction with the drawings in the implementation manner of the present application.

[0018] like Figure 1 As shown, the present application provides a method for manufacturing a high-voltage electrostatic generator cable, the method for manufacturing a high-voltage electrostatic generator cable comprising: Step 1, manufacturing a polyaromatic fiber core 1; Step 2, extruding a polyethylene insulation layer 2 outside the polyaromatic fiber inner core 1, the extrusion temperature of the polyethylene insulation layer 2 is 170-190° C.; Step 3, extruding a conductive adhesive layer 3 outside the polyethylene insulating layer 2, wherein the conductive adhesive layer 3 comprises conductive particles, a resin matrix, a dispersing additive and an auxiliary agent; Step 4, extruding a polyethylene inner sheath layer 4 outside the conductive adhesive layer 3, the extrusion temperature of the polyethylene inner sheath layer 4 is 170-190° C.; Step 5, extruding a polyvinyl chloride outer sheath layer 5 outside the polyethylene inner sheath layer 4, the extrusion temperature of the polyvinyl chloride outer sheath layer 5 is 125-160°C.

[0019] The present application can reduce the electric field stress and prevent the cable medium from being broken down by providing a layer of conductive glue outside the polyaromatic fiber inner core 1. The principle is as follows: After the conductive particles in the conductive adhesive are cured or dried, the isolation layer between the conductive particles becomes very thin due to the volatilization of the solvent and the curing of the adhesive. According to the tunneling effect of quantum mechanics, free electrons may pass through these thin isolation layers to form a conductive path, making the conductive adhesive conductive. When the conductive particles filled in the conductive glue reach a certain volume, they will contact each other to form an electronic continuity state. This state allows the free electrons on the conductive particles hit by external electromagnetic waves to move freely, forming an electromagnetic field opposite to the external electromagnetic field, thereby canceling each other out and achieving the effect of weakening electromagnetic interference waves. When the electromagnetic wave hits the free electrons of the conductive glue, heat will be generated due to the certain resistance of the conductive particles. This energy conversion process follows the law of conservation of energy, that is, the energy of the electromagnetic interference wave is converted into heat energy, thereby weakening the electromagnetic interference wave; Due to the insulating property of the resin matrix of the conductive adhesive, it can be considered that there is no direct contact between the conductive particles. Only through electron jumping between the conductive particles can the electrons pass through the insulating layer 2 to achieve the conduction effect (ie, the tunneling effect).

[0020] In the present application, a polyaromatic fiber inner core 1 is used as the conductive core of the cable, which has high conductivity and good mechanical properties. Moreover, the melting point of the relevant conductive fibers (except metal fibers) on the market is generally low (melting will occur at 200-220°C), far from meeting the flame retardant and antistatic requirements of high-voltage electrostatic generator cables above 200°C. Polyaromatic fibers have no obvious changes at 270°C, and the conductive properties begin to decline at 275°C. They are ideal materials for the inner core of high-voltage electrostatic generator cables.

[0021] It should be noted that, in the present application, the voltage of the high voltage electrostatic generator is 80-150KV.

[0022] As a preferred technical solution, manufacturing the polyaromatic fiber inner core 1 includes preparing the polyaromatic fiber, and the preparation of the polyaromatic fiber includes: Step 1, preparing a high molecular weight terephthaloyl chloride p-phenylenediamine polymer; Step 2, preparing polyaromatic fibers by liquid crystal spinning process. Liquid crystal spinning process uses fiber-forming polymers in a liquid crystal state to spin fibers. The characteristic of this process is that the spinning solution or melt is in a liquid crystal state, at which time the rigid chain polymer macromolecules are in the shape of straight rods, which is conducive to obtaining fibers with high orientation degree, and is also conducive to the most compact stacking of macromolecules in the fiber, thereby reducing defects in the fiber and greatly improving the mechanical properties of the fiber.

[0023] The preparation of high molecular weight p-phenylenediamine terephthaloyl chloride polymer includes polycondensation of p-phenylenediamine (PPD) and p-terephthaloyl chloride (TPC): Step 1, adding anhydrous lithium chloride, N-methylpyrrolidone (NMP) and hexamethylphosphoric acid triamide (HMPA) into the reactor in proportion to ensure the purity and dryness of the raw materials to avoid the influence of impurities on the polymerization reaction. In this application, the mass ratio of anhydrous lithium chloride, N-methylpyrrolidone and hexamethylphosphoric acid triamide is (4-20):100:(60-80).

[0024] Among them, anhydrous lithium chloride is used as a polycondensation reaction catalyst; N-methylpyrrolidone is used as a polycondensation reaction solvent; hexamethylphosphoric triamide is used as a polycondensation reaction solvent and an acid absorbent.

[0025] Step 2, adding p-phenylenediamine, starting the stirrer, and stirring at room temperature until the p-phenylenediamine is fully dissolved; Step 3, cooling to 0°C-15°C, adding the first batch of terephthaloyl chloride, and continuing to stir for a certain period of time (such as 30 minutes) to allow terephthaloyl chloride and p-phenylenediamine to fully react; Step 4, cool down to 0°C-15°C again, add the second batch of terephthaloyl chloride, and stir rapidly. The reaction system will show the phenomenon of climbing rods and gelling, and then the gel will be broken. At this time, the reaction should be stopped; It should be noted that carrying out the polycondensation reaction within a temperature range of 0°C-15°C can avoid the occurrence of side reactions and the reduction of polymer molecular weight.

[0026] Step 5, subjecting the reaction product in step 4 to precipitation filtration, washing and drying to remove unreacted raw materials and by-products, and obtaining a high molecular weight terephthaloyl chloride-p-phenylenediamine polymer.

[0027] It should be noted that the molecular weight and quality of the terephthaloyl chloride-p-phenylenediamine polymer product can be improved by further purifying and treating the terephthaloyl chloride-p-phenylenediamine polymer product.

[0028] As a preferred technical solution, the preparation of polyaromatic fibers by liquid crystal spinning process includes: Step 1, dissolving the prepared p-phenylenediamine terephthaloyl chloride polymer in a sulfuric acid solvent to form a liquid crystal solution. The p-phenylenediamine terephthaloyl chloride polymer has a rigid molecular structure and can form liquid crystals at an appropriate solution concentration and temperature.

[0029] Step 2, spinning is performed using a dry-jet-wet spinning process. During the spinning process, the liquid crystal solution is extruded from the spinneret hole, and the liquid crystal macromolecules are oriented themselves when passing through the air layer to obtain highly oriented polyaromatic fibers; Step 3, washing and neutralizing the obtained polyaromatic fiber; Step 4, winding the neutralized polyaromatic fiber and drying the polyaromatic fiber under traction. Under the traction, the polyaromatic fiber is stretched; at the drying temperature, the polyaromatic fiber is heat-set to further improve the performance of the polyaromatic fiber.

[0030] Furthermore, preparing the polyaromatic fiber by the liquid crystal spinning process also includes: Step 5, heat-treating the dried polyaromatic fiber in a nitrogen atmosphere at a temperature of 380° C.-420° C., so as to improve the crystallinity of the polyaromatic fiber and improve the heat resistance of the polyaromatic fiber.

[0031] Through heat treatment, the molecular chains in the polyaromatic fibers can be stacked more tightly, thereby improving the crystallinity and enhancing the physical and mechanical properties of the polyaromatic fibers; heat treatment helps to further orient the molecular chains in the polyaromatic fibers, so that the mechanical properties of the polyaromatic fibers are optimized; heat treatment can also stabilize the molecular structure of the polyaromatic fibers, thereby improving their heat resistance and allowing the polyaromatic fibers to maintain stable performance in high temperature environments.

[0032] In the present application, the crystallinity of the polyaromatic fiber before heat treatment is 94%; the crystallinity of the polyaromatic fiber after heat treatment is 96%, and the melting point is Tm=570°C.

[0033] like Figure 1 As shown, the present application also provides a high-voltage electrostatic generator cable, which includes: a polyaromatic fiber inner core 1, an insulating layer 2, a conductive adhesive layer 3 and a sheath layer.

[0034] The insulating layer 2 is coated on the outside of the polyaromatic fiber core 1. The conductive adhesive layer 3 is coated on the outside of the insulating layer 2. The conductive adhesive layer 3 comprises 40 to 50 parts of conductive particles, 35 to 45 parts of resin matrix, 4 to 6 parts of dispersing additives and 8 to 12 parts of additives by weight. Preferably, the conductive adhesive layer 3 comprises 45 parts of conductive particles, 40 parts of resin matrix, 5 parts of dispersing additives and 10 parts of additives. The sheath layer is coated on the outside of the conductive adhesive layer 3.

[0035] The present application can reduce the electric field stress and prevent the cable medium from being broken down by arranging a layer of conductive glue outside the polyaromatic fiber inner core 1 .

[0036] Specifically, the conductive particles include one or more of powdered gold, silver, copper, aluminum, zinc, iron and nickel, graphite, and conductive metal oxides; the resin matrix includes one or more of epoxy resin, silicone resin, polyimide resin, phenolic resin, polyurethane, and acrylic resin.

[0037] More specifically, the conductive particles include silver powder and copper powder in a mass ratio of (30~40): (60~70). Conductive particles silver powder and copper powder have excellent conductive properties. Silver has a very low resistivity of 1.62x10^-80•m and is not easily oxidized, so silver powder is more suitable as a conductive filler. However, due to the migration of silver powder in adhesives and the high price of silver, its application is limited. Through the above-proportioned conductive particles, the cost and conductive properties of the conductive adhesive can be taken into account.

[0038] It should be noted that in order to avoid oxidation of the copper powder, the copper powder can be treated, such as surface silver plating, adding a reducing agent, and forming a complex on the copper surface.

[0039] Specifically, the resin matrix includes cyclic hydrogen resin and acrylate resin polyurethane in a mass ratio of (30-40): (60-70). Cyclic hydrogen resin and acrylate resin polyurethane have extremely strong high temperature resistance, corrosion resistance and chemical stability. The perfluoropolymer is used as the main material of the semi-conductive adhesive, so that the semi-conductive adhesive has the properties of high temperature resistance, corrosion resistance and environmental resistance.

[0040] Specifically, the dispersing additives of the conductive adhesive include surfactants, nanomaterials, inorganic additives and other organic and inorganic compounds. The dispersing additives are used to improve the dispersibility of the conductive particles in the resin matrix to prevent the conductive particles from aggregating and affecting the conductive properties of the conductive adhesive. In the present application, the dispersing additive is carbon nanotubes. Since carbon nanotubes have strong mechanical properties, the tensile strength of the conductive adhesive can be greatly increased, and the tensile strength of the conductive adhesive can reach 1700Mpa; and since the tubular bearing effect and self-lubricating effect of carbon nanotubes have strong friction performance, acid and alkali resistance and corrosion resistance, the service life and aging resistance of the conductive adhesive are greatly improved. In addition, carbon nanotubes are also used as conductive particles to improve the conductive properties of the conductive adhesive.

[0041] As a preferred technical solution, the auxiliary agent includes one or more of a stabilizer, a plasticizer, and a catalyst. For example, the stabilizer is a German Bear brand stabilizer; the plasticizer includes dioctyl sebacate DOS; the catalyst is an imidazole compound, and the role of the catalyst in the conductive adhesive is to accelerate the curing process of the conductive adhesive so that it can achieve the desired physical and electrical properties more quickly.

[0042] As a preferred technical solution, the sheath layer includes an inner sheath layer 4 and an outer sheath layer 5, the outer sheath layer 5 is coated on the outside of the inner sheath layer 4, the material of the inner sheath layer 4 is polyethylene, and the material of the outer sheath layer 5 is polyvinyl chloride. A layer of polyethylene is tightly squeezed outside the conductive glue as an inner sheath, and its excellent electrical insulation performance can better prevent the current from being exposed. Finally, a layer of polyvinyl chloride is added to the periphery of the polyethylene as an outer sheath. The polyvinyl chloride elastic material is soft, corrosion-resistant, acid-resistant, alkali-resistant, and has good insulation properties, and is resistant to low temperatures, high temperatures, and high voltages. It can alleviate the damage to the wires in harsh climates and extend the service life of the wires. It is widely used in electrostatic spraying equipment, spinning machines, electronics, and high-voltage output test occasions to prevent backflow leakage. If an electrostatic room is provided, the amount of free static electricity in the air can be reduced and safety performance can be improved.

[0043] It should be noted that the words "first", "second" and similar words used in the specification and claims of this application do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, words such as "one" or "a" do not indicate a quantitative limitation, but indicate the existence of at least one. "Multiple" or "several" means at least two. Unless otherwise specified, words such as "front", "back", "left", "right", "bottom" and / or "top" are only for the convenience of description and are not limited to one position or one spatial orientation. Words such as "include" or "comprise" mean that the elements or objects appearing before "include" or "comprise" include the elements or objects listed after "include" or "comprise" and their equivalents, and do not exclude other elements or objects. Words such as "connect" or "connected" are not limited to physical or mechanical connections, and may include electrical connections, whether direct or indirect.

[0044] The singular forms "a", "said" and "the" used in this specification and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more of the associated listed items.

[0045] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the claims attached to this application.

Claims

1. A method for manufacturing a high-voltage electrostatic generator cable, characterized in that: The high-voltage electrostatic generator cable manufacturing method comprises: Manufacturing a polyaromatic fiber core; Extruding a polyethylene insulation layer outside the polyaromatic fiber inner core, wherein the extrusion temperature of the polyethylene insulation layer is 170-190° C.; Extruding a conductive adhesive layer outside the polyethylene insulation layer, the conductive adhesive layer comprises conductive particles, a resin matrix, a dispersing additive and an auxiliary agent; Extruding a polyethylene inner sheath layer outside the conductive rubber layer, wherein the extrusion temperature of the polyethylene inner sheath layer is 170-190° C.; A polyvinyl chloride outer sheath layer is extruded outside the polyethylene inner sheath layer, and the extrusion temperature of the polyvinyl chloride outer sheath layer is 125-160°C.

2. The method for manufacturing a high-voltage electrostatic generator cable according to claim 1, characterized in that: The manufacturing of the polyaromatic fiber inner core includes preparing the polyaromatic fiber, and the preparing of the polyaromatic fiber includes: preparing a high molecular weight p-phenylenediamine terephthaloyl chloride polymer; Preparation of polyaromatic fibers by liquid crystal spinning process; The method for preparing a high molecular weight terephthaloyl chloride-p-phenylenediamine polymer comprises: performing a polycondensation reaction of p-phenylenediamine and terephthaloyl chloride: Step 1, adding anhydrous lithium chloride, N-methylpyrrolidone and hexamethylphosphoric triamide into a reactor in proportion; Step 2, adding p-phenylenediamine, starting the stirrer, and stirring at room temperature until the p-phenylenediamine is fully dissolved; Step 3, cooling to 0°C-15°C, adding the first batch of terephthaloyl chloride, and continuing to stir for a certain period of time to allow terephthaloyl chloride and p-phenylenediamine to fully react; Step 4, cool down to 0°C-15°C again, add the second batch of terephthaloyl chloride, and stir rapidly. The reaction system will show the phenomenon of climbing rods and gelling, and then the gel will be broken. At this time, the reaction should be stopped; Step 5, subjecting the reaction product in step 4 to precipitation filtration, washing and drying to remove unreacted raw materials and by-products, and obtaining a high molecular weight terephthaloyl chloride-p-phenylenediamine polymer.

3. The method for manufacturing a high-voltage electrostatic generator cable according to claim 2, characterized in that: The method of preparing the polyaromatic fiber by liquid crystal spinning process comprises: dissolving the prepared p-phenylenediamine terephthaloyl chloride polymer in a sulfuric acid solvent to form a liquid crystal solution; The spinning process is carried out by using a dry-jet-wet spinning process. During the spinning process, the liquid crystal solution is extruded from the spinneret hole, and the liquid crystal macromolecules are oriented themselves when passing through the air layer to obtain highly oriented polyaromatic fibers. The obtained polyaromatic fiber is subjected to water washing and neutralization treatment; The neutralized polyaromatic fiber is wound up and dried under traction.

4. The method for manufacturing a high-voltage electrostatic generator cable according to claim 3, characterized in that: The method of preparing polyaromatic fibers by liquid crystal spinning process further comprises: The dried polyaromatic fiber is heat-treated in a nitrogen atmosphere at a temperature of 380° C.-420° C. to improve the crystallinity of the polyaromatic fiber and the heat resistance of the polyaromatic fiber.

5. A high voltage electrostatic generator cable, characterized in that: include: Polyaromatic fiber core; An insulating layer, the insulating layer being coated on the outside of the polyaromatic fiber inner core; A conductive adhesive layer, the conductive adhesive layer is coated on the outside of the insulating layer, and the conductive adhesive layer comprises 40-50 parts of conductive particles, 35-45 parts of resin matrix, 4-6 parts of dispersing additives and 8-12 parts of auxiliary agents by weight; A sheath layer is coated on the outside of the conductive adhesive layer.

6. The high voltage electrostatic generator cable according to claim 5, characterized in that: The conductive particles include one or more of powdered gold, silver, copper, aluminum, zinc, iron and nickel, graphite, and conductive metal oxides; the resin matrix includes one or more of epoxy resin, silicone resin, polyimide resin, phenolic resin, polyurethane, and acrylic resin.

7. The high voltage electrostatic generator cable according to claim 5 or 6, characterized in that: The conductive particles include silver powder and copper powder in a mass ratio of (30-40): (60-70); the resin matrix includes cyclopentane resin and acrylate resin polyvinyl chloride in a mass ratio of (30-40): (60-70).

8. The high voltage electrostatic generator cable according to claim 5, characterized in that: The dispersing additive is carbon nanotube.

9. The high voltage electrostatic generator cable according to claim 5, characterized in that: The auxiliary agent includes one or more of a stabilizer, a plasticizer, and a catalyst.

10. The high voltage electrostatic generator cable according to claim 5, characterized in that: The sheath layer comprises an inner sheath layer and an outer sheath layer, wherein the outer sheath layer is coated on the outside of the inner sheath layer, the material of the inner sheath layer is polyethylene, and the material of the outer sheath layer is polyvinyl chloride.